Systemic Corticosteroids Therapy in the Management of Acute Zonal Occult Outer Retinopathy - San-Ni Chen; Chang-Hao Yang; Chung-May Yang (Journal of Ophthalmology)
Purpose. To report the efficacy of systemic steroid in treating acute zonal occult outer retinopathy (AZOOR). Methods. Retrospective study of 9 consecutive patients of AZOOR, who received systemic steroid therapy in Changhua Christian Hospital from 2005 to 2013, is presented. The duration of therapy was at least 3 months. Patients were evaluated with best corrected visual acuity (BCVA), optical coherence tomography (OCT), fluorescein angiography (FA), indocyanine green angiography (ICG), visual field test, and electroretinography (ERG). Results. At the initial visit, visual field defect was noted in all patients and impaired visual acuity was noted in 4 eyes. OCT examination revealed disrupted ellipsoid zone at the macular area in 8 eyes and outer nuclear layer (ONL) loss in 1 eye. At the end of follow-up, all patients had improvement of visual field. The 4 eyes with initial impaired visual acuity had BCVA recovering to 20/20. Follow-up OCT showed partial or complete recovery of the ellipsoid zone at the macular area in the 8 eyes with initial disrupted ellipsoid zone and stable condition in the eye with ONL loss. The mean follow-up duration was 47.11±26.65 months. Conclusion. Visual improvement was achieved in most cases of recent onset AZOOR after systemic steroid treatment.